2015
DOI: 10.1155/2015/713489
|View full text |Cite
|
Sign up to set email alerts
|

Acute Aortic Occlusion Presenting as Flaccid Paraplegia

Abstract: A 67-year-old male known to be hypertensive and diabetic had a sudden onset of severe low back pain and flaccid paraplegia with no sensory level or bladder affection and the distal pulsations were felt. Acute compressive myelopathy was excluded by MRI of the dorsal and lumbar spines. The nerve conduction study and CSF analysis was suggestive of acute demyelinating polyneuropathy. The patient developed ischemic changes of the lower limb and CT angiography revealed severe stenosis of the abdominal aorta and both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…[15][16][17][18] One study concluded that obese patients had higher levels of procoagulant particles and increased thrombin generation which lead to hypercoagulability. 2 In addition, obese patients are even more hypercoagulable after injury or trauma. 15 Smoking is a well-known risk factor for small vessel disease and studies have shown that smoking drastically affects aortic integrity due to increased levels of proteases, chronic inflammatory infiltration, and dysfunction to aortic matrix repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18] One study concluded that obese patients had higher levels of procoagulant particles and increased thrombin generation which lead to hypercoagulability. 2 In addition, obese patients are even more hypercoagulable after injury or trauma. 15 Smoking is a well-known risk factor for small vessel disease and studies have shown that smoking drastically affects aortic integrity due to increased levels of proteases, chronic inflammatory infiltration, and dysfunction to aortic matrix repair.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Advanced peripheral artery disease typically presents with the classic “Five P’s” of pain, pallor, pulselessness, paralysis, and paresthesia. 2 The level at which the arterial occlusion occurs thus manifests with signs of ischemia distal to the site of occlusion: possibly affecting extremities, spinal cord, intestines, and/or kidneys. 3 Notable symptoms include claudication and rest pain, although unusual presentations such as paraplegia have also been described as a result of aortic occlusion around the level of the artery of Adamkiewicz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAO is generally mistaken as neurological disorders and is missed up to 50% of cases presenting with paraplegia. [31] Complete occlusion of an artery without adequate collaterals is characterized by the six Ps, pain, pallor, pulselessness, paresthesia, paralysis, and prostration. [32] The classic five P's, pain, pallor, pulselessness, paralysis, and paresthesia can be diagnostic of AAO.…”
Section: Excessive Day Time Sleep and Night Awakeningmentioning
confidence: 99%
“…[32] The classic five P's, pain, pallor, pulselessness, paralysis, and paresthesia can be diagnostic of AAO. [31] Even though pallor and pulselessness are not found in Urustambha lakshanaa, it can be assumed that predominance of kapha and medas will cause pallor and pulselessness also along with pain, paresthesia, and paralysis. By considering the above facts, it seems that signs and symptoms of aortoiliac occlusion or AAO are similar to Urustambha lakshanaa [ Table 3].…”
Section: Excessive Day Time Sleep and Night Awakeningmentioning
confidence: 99%